Both monovalent cations and plectin are potent modulators of mechanical properties of keratin K8/K18 networks. Issue 33 (4th August 2016) - Martin, I.; Moch, M.; Neckernuss, T.; Paschke, S.; Herrmann, H.; Marti, O.
Abstract : The effect of monovalent cations and plectin on the architecture and mechanical properties of keratin K8/K18 networks. Abstract : Intermediate filament (IF) networks are a major contributor to cell rigidity and thus serve as vital elements to preserve the integrity of entire cell layers. Keratin K8 and K18 IFs are the basic constituents of the cytoskeleton of epithelial cells. The mechanical properties of K8/K18 networks depend on the structural arrangements of individual filaments within the network. This paper investigates the architecture of these networks in vitro under the influence of the monovalent cation potassium and that of the cytolinker protein plectin. Whereas increasing amounts of potassium ions lead to filament bundling, plectin interlinks filaments at filament intersection points but does not lead to bundle formation. The mechanics of the resulting networks are investigated by microrheology with assembled K8/K18 networks. It is shown that bundling induced by potassium ions significantly stiffens the network. Furthermore, our measurements reveal an increase in plectin-mediated keratin network rigidity as soon as an amount corresponding to more than 20% of the plectin present in cells is added to the keratin IF networks. In parallel, we investigated the influence of plectin on cell rigidity in detergent-extracted epithelial vulva carcinoma derived A431 cells in situ . These cytoskeletons, containing mostly IFs, actin filaments and associated proteins, exhibit a significantly decreased stiffness, when plectin is downregulated to ≈10% of the normal value. Therefore, we assume that plectin, via the formation of IF–IF connections and crosslinking of IFs to actin filaments, is an important contributor to cell stiffness.